Pengaruh Digital Marketing, Word Of Mouth dan Brand Awareness Terhadap Purchase Decision Produk Livin’ By Mandiri Pada PT. Bank Mandiri (Persero) Tbk di Kantor Cabang Sumbawa - Muhammad Mujahid Nasrullah; Sherwin Ary Busman (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research aims to examine the effect of digital marketing, word of mouth and brand awareness on purchase decisions for livin' by mandiri products at PT. Bank Mandiri (Persero) Tbk at the Sumbawa Branch Office. This research uses a quantitative method with an associative approach. Determination of the sample in this research using the Paul Leddyâ€™s formula through non-probability sampling technique with purposive sampling method and obtained a total of 96 research samples. The sampling method was obtained through a non-probability sampling technique with a purposive sampling method. The data analysis technique in this research used multiple linear regression analysis and the analysis tool used was the Statistical Program for Social Science (SPSS) 25 for windows application. The results of the analysis in this research indicate that digital marketing, word of mouth and brand awareness partially have a positive and significant effect on purchase decisions.Â